(untitled) (Global Journal of Science Frontier Research, 2014)
Transportation Algorithm uses for solving Transportation Problem to find feasible solution which may optimal or not. This is now a challenge that developed such an algorithm which gives optimal solution without using Optimality Methods like as MODI, Stepping-Stone. For this reason there are several transportation algorithm exists for solving TP like as North West Corner Rule (NWC), Least Cost Method (LCM), Vogel’s Approximation Method (VAM) etc. where VAM provides the feasible solution which is lower than NWC and LCM and for some case of TP it coincides with optimal solution. In this paper we proposed a new approach named "Implied Cost Method (ICM)" where feasible solutions are lower than VAM and very close to optimal solution or sometimes coincides with optimal solution.